Identifikasi Ketidaksesuaian Mutu Pekerjaan Arsitektur Pada Pembangunan Rumah Sakit X di Surabaya - Farisi, Iqbal Al (Jurnal Vokasi Teknik Sipil, 2023)
As one of the developing countries, Indonesia carries out infrastructure development which aims to provide facilities for all levels of society. One of the infrastructures built is a health building or hospital. The ongoing construction of a hospital is X hospital in Surabaya. The quality of the results of work on hospital construction projects is very concerned, so that quality can be achieved as desired. However, it is possible that there is work that is not in accordance with quality. This study aims to identify and find out what are the discrepancies in the quality of architectural work at X Hospital in Surabaya. The method used is field observation. The results of this study were found to be quality discrepancies in 68 findings in ceramic work, 60 findings in ceilings, 8 findings in stair railings, 5 findings in walls, 4 findings in sills and 3 findings in sanitary ware with a total of 148 defects. The types of quality discrepancies found were misaligned ceramics, hollow, broken, less strong ceiling frames, hairline cracks in the ceiling, wet, untidy railling finishing joints, hairline cracked walls, inaccurate wall angles, improper installation of sills, cracked sealants and installation of sanitary ware less tight. It is known that the cause of the discrepancy in the results of the work comes from the implementation of work that is not properly supervised.